Water treadmill training protects the integrity of the blood-spinal cord barrier following SCI via the BDNF/TrkB-CREB signalling pathway. (February 2021) - Ying, Xinwang; Xie, Qingfeng; Yu, Xiaolan; Li, Shengcun; Wu, Qiaoyun; Chen, Xiaolong; Yue, Jingjing; Zhou, Kecheng; Tu, Wenzhan; Jiang, Songhe
Abstract: Following spinal cord injury (SCI), destruction of the blood-spinal cord barrier (BSCB) leads to increased microvascular permeability and tissue oedema. The BSCB, formed by a dense network of tight junctions (TJs) and adhesion junctions (AJs) is considered a therapeutic target. Most studies have focused on the effect of drug therapy on the neurovascular system after SCI, ignoring the protection and functional recovery of the vascular system by exercise training. Previously, we indicated that water treadmill training (TT) has a protective effect on the BSCB after SCI, but the specific molecular mechanism of the effect of TT on BSCB is still not clear. In this study, we used a specific inhibitor of TrkB (ANA-12) to explore whether the BDNF/TrkB-CREB signalling pathway is involved in TT-mediated BSCB protection after SCI. A New York University (NYU) impactor was used to establish the SCI model. Rats in the SI (Sham + ANA-12), IM (SCI + ANA-12) and ITM (SCI + TT + ANA-12) groups were injected with ANA-12 (0.5 mg/kg) daily, and rats in TM (SCI + TT) and ITM (SCI + TT + ANA-12) groups were treated with water TT for 7 or 14 d. The degree of neurological deficit, water content, BSCB permeability, protein expression and ultrastructure of vascular endothelial cells were assessed by the Basso-Beattie-Bresnahan (BBB) motor rating scale, Evans blue (EB), Western blot (WB) experiments, immunofluorescence and transmission electron microscopy (TEM). Our results suggest that TT upregulates the BDNF/TrkB-CREB signalling pathway following SCI. The BDNF/TrkB-CREB signalling pathway is involved in the protection of the BSCB. Application of the inhibitor blocked the protective effect of TT on the BSCB. We concluded that TT ameliorated SCI-induced BSCB impairment by upregulating the BDNF/TrkB-CREB signalling pathways.